Acne fulminans and Cutibacterium acnes phylotypes. (16th January 2020) - Bocquet‐Trémoureux, S.; Corvec, S.; Khammari, A.; Dagnelie, M.‐A.; Boisrobert, A.; Dreno, B.
Abstract: Background: Acne fulminans (AF) is a rare and severe form of inflammatory acne. It is characterized by a sudden worsening of acne with appearance of ulceronecrotic lesions, which can be associated with systemic signs. Its pathophysiology and the best therapeutic strategy are only partially known. Objective: Our main objectives were to describe the clinical and biological profile of AF patients and to determine whether there was a difference in Cutibacterium acnes phylotype in AF compared to acne vulgaris. The secondary objective was to assess the efficacy of different therapies. Methods: A retrospective observational study was conducted in all patients followed for AF in our department between 2008 and 2018. Bacteriological samples were taken from each patient to analyse C. acnes phylotype distribution. The therapeutic response was assessed using the ECLA and GEA scales. Results: Fifteen patients with a median age of 15 years were included (12 men, 80%). A family history of acne was found in 86.7% of patients. Nine patients (60%) had isotretinoin‐induced AF. Only one patient (6.7%) showed systemic signs. The bacteriological culture was positive for C. acnes in 80% of patients. The predominant phylotype was IA1 in 60% of patients, corresponding to the predominant phylotype in acne vulgaris. Only 33.3% of patients were in remission after a first‐line treatment with systemic corticosteroids, alone or in combination. Seven patients were treated with biotherapy, including five successfully with secukinumab. Conclusion: Our results suggest that there is no specific C. acnes phylotype associated with AF, raising the hypothesis that acute inflammation associated with AF may be more related to an abnormal cutaneous innate immunity activation. The use of preventive strategies, the impact of combined treatments and an assessment of the role of biotherapies, especially anti‐IL‐17, in AF treatment remain to be more investigated.